Linking altered neuronal and synaptic properties to nicotinic receptor Alpha5 subunit gene dysfunction: a translational investigation in rat mPFC and human cortical layer 6 - Danqing Yang; Guanxiao Qi; Daniel Delev; Uwe Maskos; Dirk Feldmeyer (Translational Psychiatry)
Abstract Genetic variation in the α5 nicotinic acetylcholine receptor (nAChR) subunit of mice results in behavioral deficits linked to the prefrontal cortex (PFC). rs16969968 is the primary Single Nucleotide Polymorphism (SNP) in CHRNA5 strongly associated with nicotine dependence and schizophrenia in humans. We performed single cell-electrophysiology combined with morphological reconstructions on layer 6 (L6) excitatory neurons in the medial PFC (mPFC) of wild type (WT) rats, rats carrying the human coding polymorphism rs16969968 in Chrna5 and α5 knockout (KO) rats. Neuronal and synaptic properties were determined for the three rat genotypes. Compared with neurons in WT rats, L6 regular spiking (RS) neurons in the α5KO group exhibited altered electrophysiological properties, while those in α5SNP rats remained unchanged. L6 RS neurons in mPFC of α5SNP and α5KO rats differed from WT rats in dendritic morphology, spine density and spontaneous synaptic activity. Galantamine was applied to identified L6 neuron populations to specifically boost the nicotinic responses mediated by α5*nAChRs. Remarkably, it restored nicotinic modulation in neurons of α5SNP rats, while no such effect was observed in α5KO rats. Additionally, galantamine functioned as a positive allosteric modulator of α5*nAChRs in RS neurons, both in rat and human cortical L6, but did not affect burst spiking (BS) neurons. Our findings suggest that dysfunction in the α5 subunit gene leads to aberrant neuronal and synaptic properties, shedding light on the underlying mechanisms of cognitive deficits observed in human populations carrying α5SNPs. They highlight a potential pharmacological target for restoring the relevant behavioral output.